Pemberdayaan Temporer: Kritik Sosiologis terhadap Program Anugerah Desa Wisata Indonesia di Kabupaten Gowa: Temporary Empowerment: A Sociological Critique of the Indonesian Tourism Village Award Program in Gowa Regency - Nur Riswandy Marsuki (Emik : Jurnal Ilmiah Ilmu-Ilmu Sosial, 2026)
The development of tourist villages in recent years has become one of the government's main strategies in encouraging locally based economic growth while strengthening the independence of village communities. Unlike previous research, which generally focused on tourism potential, economic impact, community participation, and the success of government programs in developing tourism villages, post-program sustainability and the commodification of empowerment in the context of tourism villages are still relatively limited in the existing literatures, this study deals with  post-program dynamics, particularly regarding the sustainability of community empowerment following the implementation of the Indonesian Tourism Village Award program, initiated by the Ministry of Tourism and Creative Economy since 2021. It aims to uncover the discrepancy between program objectives and empirical realities on the ground, where empowerment tends to be temporary and unsustainable.  This qualitative research with a case study approach was conducted in Manuju Tourism Village, Gowa Regency. Data were collected through in-depth interview and field observation. There were 11 informants participated in this study, consisting of a village head, village secretary, Pokdarwis chairman, Karang Taruna members, social activists, business actors (MSMEs), two waterfall managers, and three community members.  The findings indicate that, following the program's completion, empowerment activities stagnated and declined, reflected in the weakening of local institutions (Pokdarwis), declining community participation, and limited ongoing government support. These findings indicate that empowerment within the program tends to be temporary and performative, oriented more toward meeting competition-based indicators than fostering long-term social transformation. From a sociological perspective, this condition reflects the commodification of empowerment, where empowerment practices are constructed as part of the program's representation rather than as a sustainable, community-driven process. Therefore, this study recommends a reorientation of program design from a competition-based model toward a sustainable facilitation approach, which emphasizes building community capacity and capabilities, as well as institutionalizing participation through strengthening local institutions.